2016
DOI: 10.1186/s12284-016-0091-8
|View full text |Cite
|
Sign up to set email alerts
|

Allele-specific marker-based assessment revealed that the rice blast resistance genes Pi2 and Pi9 have not been widely deployed in Chinese indica rice cultivars

Abstract: BackgroundThe most sustainable approach to control rice blast disease is to develop durably resistant cultivars. In molecular breeding for rice blast resistance, markers developed based on polymorphisms between functional and non-functional alleles of resistance genes, can provide precise and accurate selection of resistant genotypes without the need for difficult, laborious and time-consuming phenotyping. The Pi2 and Pi9 genes confer broad-spectrum resistance against diverse blast isolates. Development of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 37 publications
2
42
1
Order By: Relevance
“…The employed marker details such as primer sequences and distance to target gene are provided in Table 1 Blast is the most dangerous fungal disease. Tian et al (2016) assessed a set of 434 Chinese rice cultivars and breeding materials for the Pi9 gene and found that none of the screened rice materials had Pi9, which is in close agreement with the present study. More than 100 blast resistance genes have been reported and, among them, Pi9, Piz-t, and Pib are a few of the important genes that provide resistance to a wide range of M. grisea isolates (Wang et al, 1999;Qu et al, 2006;Zhou et al, 2006).…”
Section: Screening Of Diverse Rice Accessions For Rice Blast and Bb Dsupporting
confidence: 90%
“…The employed marker details such as primer sequences and distance to target gene are provided in Table 1 Blast is the most dangerous fungal disease. Tian et al (2016) assessed a set of 434 Chinese rice cultivars and breeding materials for the Pi9 gene and found that none of the screened rice materials had Pi9, which is in close agreement with the present study. More than 100 blast resistance genes have been reported and, among them, Pi9, Piz-t, and Pib are a few of the important genes that provide resistance to a wide range of M. grisea isolates (Wang et al, 1999;Qu et al, 2006;Zhou et al, 2006).…”
Section: Screening Of Diverse Rice Accessions For Rice Blast and Bb Dsupporting
confidence: 90%
“…Pyramiding rice blast resistance genes has been becoming an effective strategy to develop a new variety with long lasting resistance. Currently, several broad-spectrum resistance genes such as Pi9 , Pi2 , Pizt , and Pi54 , have already been cloned, but their distribution frequencies in elite parents of Chinese indica and japonica rice were low (Huang et al, 2015; Wu et al, 2015; Tian et al, 2016). Moreover, research in levels of resistances to leaf and panicle blasts of rice plants pyramiding either Pi9 or Pizt , and Pi54 hasn’t yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tian et al. () reported the development of an InDel marker and a CAPS marker for genotyping of Pi2 and Pi9 targeting the Pi2/Pi9 locus; Scheuermann and Jia () also developed a dominant marker to identify Pi9 ‐containing rice germplasm. In the study, we report on the development of a gene‐targeted and codominant marker for discriminating the Pi2 and Pi9 genes.…”
Section: Discussionmentioning
confidence: 99%
“…These four allelic R genes, Pi2 , Piz‐t and Pi50 were isolated from Oryza sativa , while the Pi9 was originated from Oryza minuta . Though they had been characterized for years, the R genes Pi2 and Pi9 have not yet been widely deployed in rice breeding programmes (Tian et al , Scheuermann and Jia ).…”
mentioning
confidence: 99%